Motor Learning Process of Virtual Reality Tasks with Different Demands in Post Stroke Individuals - Jangarelli,Giovanna C. (2019)
Practicing tasks in Virtual Reality (VR) environment has shown to be effective for gain in cognitive and motor functions in post stroke individuals. However, there are few information about how the motor learning process of tasks with different demands occurs in this population, and if there are differences when compared with healthy individuals. The aim of the present study was to investigate the motor learning process of eight VRs tasks with different cognitive and motor demands, in post stroke individuals (Experimental Group-EG), and compare it with healthy individuals (Control Group-CG). Eighteen individuals participated in the study performing eight sessions of practice, four for each task. The study involved: pre-test (1 session), acquisition phase (4 sessions for each task), post-test (1 session), and retention test (1 session after thirty days since the end of acquisition phase). The statistical analysis was run by a 2 x 3 ANOVA (groups x learning tests) with Tukey post hoc. At the end, EG group was able to learn three tasks, while CG learned four, one more than the ones learned by the post-stroke individuals. Tasks complexity affected, in more intensely the motor learning process in post-stroke individuals that with eight sessions were able to learn only low-complexity tasks.